O domínio de si mesmo (εγκράτεια) como condição ético-existencial na filosofia de Platão - Rocha, Gabriel Rodrigues (2015)
From the understanding of two particular sentences VII of the Charter (331 d): "Live each day so that was master of himself (ἐγκρατῂς αὐτὸς αὑτοὗ) as much as possible; "And (c 324):" When I was young, I felt the same as many: I thought, soon I became lord (κύριος) of myself, go straight to the policy; "The thesis intended to propose how the concept of εγκράτεια (self-control) is of exceptional importance throughout the Platonic philosophy, at different stages in the production-written dialogue of the Athenian philosopher. It suggests that Plato shows a real philosophical intentionality, not only with the formation of self-control to those who intend "to go" policy, but also extending this training to the interior individuality of each participant in the political community; likewise, it was proposed that the other domain ultimately present as a corollary of knowledge and self care, taking them to these as essentially members of Platonism concepts. It concludes that self-control is a power higher college ψυχή, and so it is a virtue and a purification of themselves capable of being trained / configured on each psychic individuality, constituting as well as spiritual exercise par excellence. The purpose of this practice himself never appears as pure theoretical training, but is also always an activity, a continuous movement that prepared the ethical, political and existential conduct humanly possible.